Bonding mechanism of cold-sprayed TiO2 coatings on copper and aluminum substrates - Omar, Nooririnah; Yamada, Motohiro; Yasui, Toshiaki; Fukumoto, Masahiro (MDPI AG, 2021)
The cold spraying of ceramic materials is widely acknowledged as a difficult process because it necessitates the feedstock powder particles experiencing a plastic deformation for deposition on a substrate. The problem arises due to the brittle properties of ceramic powder feedstock such as titanium dioxide (TiO2), combined with a lack of understanding of the bonding mechanisms. In this study, TiO2 coatings were deposited onto copper and aluminum substrates and the adhesion strength was evaluated to investigate the bonding mechanism. The influence of substrate hardness and remaining surface oxide layer was investigated by annealing the substrates with various temperatures. The results showed that the adhesion strength of the coatings on the aluminum substrate was higher than the copper substrate. Furthermore, the adhesion strength was decreased with increasing the annealing temperature on both substrate materials. These results indicate that a softer aluminum substrate was advantageous for adhesion. Annealing led to thermal softening the substrate; however, the thickness of the surface oxide layer was increased. Therefore, bonding occurred between the cold-sprayed TiO2 particle and newly deform substrate surface, which yielded the higher adhesion strength. The main bonding mechanism is metallurgical, similarly to the colds-prayed metallic coatings